Computational assessment of structural stability of E protein variants in coronaviridae - Teo, Valerie Fang Wei (Nanyang Technological University, 2022)
Studies on coronaviruses have received spotlight due to the CoVID-19 pandemic. These studies range from determining the structure of the protein, pathway of infection to exploring therapeutic targets within the protein. Although E protein has been proven critical for viral assembly and maturation and is completely conserved in genomes of all four genera of the coronaviridae, little is known about the function of the smallest protein encoded in SARS-CoV-2. There are many uncertainties regarding reliability of Swiss Model predicting its 3D structure though it is the most used homology modelling server. In this study, Molecular Dynamics simulation was performed for 1 sequence per genus to check their stability in a lipid bilayer using GROMACS. The primary focus is to identify the most thermostable sequence variant of E protein with the greatest potential for structural and drug discovery studies. Results showed that the sequence from Delta genera was the most stable, followed by Beta, Alpha then Gamma. Although conclusion derived from Swiss Model and simulations were the same, the simulations were more informative and reliable. Findings presented provide an alternative to traditional homology modelling and provide a deeper understanding to E proteins stability and their amenability to structural and relationship studies.